Recent Progress in Solar‐Blind Deep‐Ultraviolet Photodetectors Based on Inorganic Ultrawide Bandgap Semiconductors. (7th January 2019) - Xie, Chao; Lu, Xing‐Tong; Tong, Xiao‐Wei; Zhang, Zhi‐Xiang; Liang, Feng‐Xia; Liang, Lin; Luo, Lin‐Bao; Wu, Yu‐Cheng
Abstract: Due to its significant applications in many relevant fields, light detection in the solar‐blind deep‐ultraviolet (DUV) wavelength region is a subject of great interest for both scientific and industrial communities. The rapid advances in preparing high‐quality ultrawide‐bandgap (UWBG) semiconductors have enabled the realization of various high‐performance DUV photodetectors (DUVPDs) with different geometries, which provide an avenue for circumventing numerous disadvantages in traditional DUV detectors. This article presents a comprehensive review of the applications of inorganic UWBG semiconductors for solar‐blind DUV light detection in the past several decades. Different kinds of DUVPDs, which are based on varied UWBG semiconductors including Ga2 O3, Mgx Zn1− x O, III‐nitride compounds (Al x Ga1− x N/AlN and BN), diamond, etc., and operate on different working principles, are introduced and discussed systematically. Some emerging techniques to optimize device performance are addressed as well. Finally, the existing techniques are summarized and future challenges are proposed in order to shed light on development in this critical research field. Abstract : Recent advances in developing solar‐blind deep ultraviolet light (DUV) photodetectors based on various inorganic ultrawide‐bandgap semiconductors are reviewed, such as Ga2 O3, Mg x Zn1− x O, III‐nitride compounds (Al x Ga1− x N/AlN and BN), and diamonds.